Advanced Abdominal Pregnancy of 32 Weeks with Alive Baby: A Rare Event - Malik, Adiba (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Abdominal pregnancy is a rare form of ectopic or extrauterine pregnancy with an incidence of 1:10000 and 1:30000. Advanced abdominal pregnancy is extremely rare with high maternal and perinatal mortality. Case Presentation: We report a case of abdominal pregnancy at 32 weeks gestation with persistent abdominal pain and severe anemia, who was referred from another hospital to our center with an Ultrasonogram, missed the diagnosis of abdominal pregnancy, which was confirmed in our center as abdominal pregnancy at 32 weeks with live fetus. With laparotomy a 1.2 kg female baby was born without much difficulty and post operative recovery was uneventful. But the baby died at 27Th post operative day. Conclusion: High index of clinical suspicion is necessary for early diagnosis of abdominal pregnancy and timely laparotomy with multidisciplinary surgical team can save the life of a mother. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 76-78